Pre-service teacher education may perpetuate myths about teaching and learning. Issue 3 (26th May 2020) - Rogers, John; Cheung, Anisa
ABSTRACT: This research report presents the preliminary findings of mixed-methods study examining the beliefs of trainee teachers regarding a number of 'learning myths', e.g., learning styles and multiple intelligences. Using a cross-sectional experimental design, survey data were collected from 65 pre-service teachers enrolled in a high-profile Bachelor of Education program as to their beliefs in a number of myths about teaching and learning. 18 participants then took part in semi-structured interviews. The results indicate that trainee teachers' beliefs in education myths and misconceptions may not change over the course of a five-year 'evidence based' teacher preparation program. Further, the qualitative results suggest that beliefs in learning myths might become further entrenched over the course of study as a result of being actively promoted by faculty throughout the program.